Kalam Aktual: Upaya Revitalisasi Ilmu Kalam - Muhammad In'am Esha (el Harakah: Jurnal Budaya Islam, 2004)
The science of Kalam (Islamic theology) is a historical product which needs to be discussed and restored its ‘elan vital’. Its strategic position and content, since it directly relates to human’s fundamentalism aspect (human’s belief principles), should not be considered as something ‘holy’ and ‘sacred’. Kalam is no other than the experts’ manifestation of sense of social crisis in responding the problematic and mainstream thought at the time. Hence, in the mid of modern phenomenon, the challenge and mainstream thought faced by Moslem is a fate to hold a reposition and revitalization (actualization) of ‘elan vital’ of Kalam science. Each Moslem has an obligation to learn about the recent issues regarding pluralism and humanity crisis and to put it into a serious discussion in a modern perspective. Ilmu kalam adalah produk historis yang perlu untuk dikaji ulang dan dikembalikan elan vital-nya. Posisi dan kandungannya yang strategis, karena sangat bersentuhan dengan aspek fundamental manusia (pokok-pokok keyakinan manusia), hendaknya tidak dipandang sebagai sesuatu yang suci dan sakral. Ilmu kalam tidak lain merupakan manifestasi sense of social crisis para pemikir dalam merespon problematika dan mainstream pemikiran pada zamannya. Oleh karena itu, di tengah berbagai fenomena kekinian, tantangan dan mainstream pemikiran yang tengah dihadapai umat Islam adalah sesuatu yang niscaya untuk mengadakan reposisi dan revitalisasi (aktualisasi) elan vital ilmu kalam. Setiap Muslim diharuskan untuk mempelajari isu-isu terkini mengenai pluralism dan krisis kemanusiaan dan mendiskusikannya dalam perspektif era kontemporer.